MINIMIZING PHONOLOGICAL [SUPRASEGMENTAL] ERRORS IN READING ALOUD USING CALED - Pariana, I Nengah (Borneo Journal of English Language Education, 2019)
In order to minimize students? errors in producing their vowel quality, stress, and intonation, a one-shoot action research was employed. The subjects of this study were 10 students of XII Hotel Accommodation who were failed in Reading Aloud competence. By drilling them using CALED, the students? errors in stress and vowel quality have been decresed significantly.? But, intonation produced by students was slightingly still influenced by their Indonesian.